Sequence Analysis of Macaca mulatta TRIM4 and Its Role in the Interferon Pathway - Zhao, Mengmeng; Li, Huawei; Zhang, Hang; Sha, Huiyang; Huang, Liangzong; Wang, Ruining (Frontiers in Veterinary Science, 2022)
Monkey diseases are becoming increasingly severe, and some may be transmitted to humans through direct and indirect contact. Innate immunity is the first line of defense against foreign microorganisms. It is of great significance to explore the immune characteristics of monkey and human diseases. TRIM4, an important immune molecule in Macaca mulatta, was cloned and its immunological characteristics were preliminarily explored. The results showed that Macaca mulatta TRIM4 was in the same branch as human TRIM4. Overexpression of TRIM4 increased the mRNA levels of interferon (IFN)-alpha, IFN-beta, RIG-I, MAVS, IRF3, IRF7, OAS1, IFIT3, and CCL5, TRIM4 up-regulated the activities of IFN-beta, NF-κB, and ISRE reporter. In contrast, inhibiting TRIM4 expression by small interfering RNA (siRNA) down-regulated the IFN pathway. In summary, Macaca mulatta TRIM4 plays an essential role in the IFN pathway.